(3GdMdd GdHgjI aj edhc GdOhdI GdYdhjIs - (3CHh YHO Gddg eMeO Hf eMeO Hf GdeUWai GdeTQaj GdMSfj GdEZQjSj,J (B1334 (3g` s
(3ChdgG (B:s
(3hHYO adeG hbaJ Ydi bUjOI GdcGJH GdCOjH GdBJj PcQg ai GdebOeI ai YgO edhc ef GdOhdI GdYdhjI GdeNJUI HeaGNQI LeI s
(3BNQgG (B:s
(3hbO UGQ edcg dg HGdgOjI ef Gdedhc ceG gi YGLOI Gdedhc GdYXGe, hgh CjVkG ef eYGfj GEYJRGR ef GdLGfH ai bHdg hcGf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B178 - (3U(B497s
(3hgh TQM Ydi fXe CHj GdeYGdj Hf GdeGdcj Hf CMeO Hf SdejGf GdCfOdSj GdaGSj GdeJhaj SfI (B1310(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B76s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B153 ; (3agQSJ GdNRGfI GdYGeI HGdQHGW (B- (3GdLRA (B2 - (3U (B114 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJGQjNs